Estradiol-to-testosterone ratio and erectile dysfunction in men aged 35-45 - Georgi V. Lazarov (Folia Medica)
Aim: This study investigated the relationship between erectile dysfunction and the estradiol-to-testosterone ratio in men aged 35 to 45. Materials and methods: Screening procedures were designed to select eugonadal men between 35 and 45 years of age to evaluate the impact of the estradiol-to-testosterone ratio on the development of erectile dysfunction. Out of 1,521 patients examined in the andrology office for erectile dysfunction between January 2013 and December 2019, a total of 73 men were included for evaluation. Erectile dysfunction was evaluated using the International Index of Erectile Function (IIEF). Twenty age-matched men without erectile dysfunction were randomly selected to form the control group. We measured the total serum testosterone level three times, every 45 days, for three months, and measured estradiol once at the third blood collection. Results: Among the patients with erectile dysfunction, we observed the estradiol-to-testosterone ratio values ranging from 0.0042 to 0.0110. These values were significantly higher than those of the control group (0.0015–0.0020) (p<0.001). There were significant differences in the questionnaire score between the patients and the control group (p<0.001). We did not observe fluctuations in the blood flow to the artery profunda of the penis bilaterally during color Doppler ultrasound. Conclusion: Our study suggests that erectile dysfunction in men aged 35 to 45 years may be associated with an estradiol-to-testosterone ratio of 0.0041–0.0110. In the clinical examination of these patients, it is necessary to test for estradiol in addition to testosterone.